E-Health - for continuity of care: proceedings of MIE2014 - Lovis, Christian (Studies in health technology and informatics, 2014)
Information technology and the information sciences have been part of our lives for some time now. They have revolutionized the healthcare system, changing the whole health landscape, as well as health culture. New devices, sources of data and roles ...
Keywords: Konferenzschrift